Perceptions, Attitudes, and Barriers to scientific publications among medical college staff members - A cross-sectional study - Vijaya Shankargouda Dandannavar; Jyoti Nagamoti; Ashwini Narasannavar; Nirmala Anand (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: In the medical profession to improve health care, there is a need to conduct valid and reliable research work and that doctors, nurses, and other care workers play an important role in health care. Attitude and perceptions have a significant impact on staff performance, which, in turn, decides the performance of the organization. There is a need for the provision of the requirements of researches, which would bolster their enthusiasm and improve the attitude and research productivity AIM: The aim of this study is to find out the publishing practices, perceptions, attitudes, and barriers regarding scientific publications among pre and para clinical faculties. MATERIALS AND METHODS: Institutional Ethical committee (IEC) was obtained, and a prevalidated structure questionnaire which had four sections pertaining to sociodemographic status, perception, attitudes, and barriers was used to collect the required data from 57 faculty members, willing to participate in the study, and the questionnaire was administered after taking voluntary informed consent from them RESULTS: About 31.60% of participants manuscript were rejected, and among them, the reasons for rejections were no new knowledge, not of journal interest, similar studies were published earlier published, inappropriate title, study was simple and plain and such studies were not published, sample size inadequate, no correct reasons given by the reviewers, inappropriate methodology, not well scripted, not as per the scope of the journal, lots of pending articles, and inappropriate statistic's used. Fifty-six percent of the total faculty were primed about the Basics of the Research Methodology and that 53% of participant's felt that research Methodology and training for the research in the medical field will be useful and would improve the standard of research productivity. More than 50% of the study participants were of the opinion the Post graduates should learn more about and conduct research in a scientific way. Twenty-five percent of the study participants were of the opinion that getting involved in research will over burden them. Majority of the study participants felt that motivation to take up research by receiving timely incentives for publication's would persuade them to take up research. Thirty-six percent of the Participants felt that the reasons for the nonindulgence in research were personal and 21% were inclusive regarding the availability of resource's for conducting the research. CONCLUSION: Major barrier to publications was financial aspects and the unavailable resources though it was considered important for the promotions and future prospects. Majority of the medical faculty were of the opinion that Research methodology and training in the medical field will improve the standard of teaching. In order to increase the no of the faculty publications the barriers both at the individual and institutional levels can be overcome by giving suitable incentives to the faculty members and encourage them to publish by providing all the resources needed and free excess to the information as well.